KETAHANAN KELUARGA SEBAGAI FONDASI MASYARAKAT SEJAHTERA - Fazil , Muhammad (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2025)
Family is the smallest unit of society that plays a strategic role in creating a prosperous civilization. Family resilience becomes an important foundation for the stability and harmony of society. This research aims to explore the four main pillars in strengthening family resilience, namely piety, patience, affection, and adequate livelihood, as well as to identify the main factors triggering divorce, such as early marriage, the presence of a third party, poverty, and lack of religious knowledge. These four pillars serve as guidelines for building a harmonious, stable, and religious family relationship. Taqwa strengthens the family's spiritual connection, patience serves as a foundation in facing conflicts, affection creates strong emotional bonds, and adequate livelihood ensures material well-being. On the other hand, the factors triggering divorce often stem from emotional unpreparedness, economic pressure, and a lack of religious understanding. This research provides practical solutions to address these challenges, including through premarital education, skills training, and enhancing religious understanding within the family. By implementing these strategies, it is hoped that families can become strong bastions that support the creation of a harmonious and prosperous society. In conclusion, family resilience is the key to social sustainability and stability.